Curvature combs and curvature plots. (November 2016) - Farin, Gerald
Abstract: We compare curvature combs and curvature plots. Highlights: We explored some properties of curvature combs. We found that due to their 3D nature, they may be hard to interpret. Curvature plots might be more appropriate in some situations.